Comparison of oral fibre optic intubation using parker flex tip tracheal tube and unoflex reinforced tracheal tube during general anaesthesia - Narhari, Rupesh A/L (2018)
Background: The choice of endotracheal tube (ETT) is important for the success of orotracheal fibreoptic intubation (OFI). The aim of the study was to compare the use of Parker Flex Tip® (PFT) ETT with Unoflex™ Reinforced (UFR) ETT during oral fibreoptic intubation. Method: A total of 58 patients who underwent elective surgery under general anaesthesia were randomised into two groups for OFI after successful induction and application of rigid cervical collar for difficult airway simulation. Group A (n=29) was intubated with PFT ETT and Group B (n=29) was intubated with UFR ETT. All patients were induced with standard dose of intravenous (IV) Fentanyl 2 μg/kg and IV Propofol 2 mg/kg, and were paralysed with IV Rocuronium 0.6 mg/kg. OFI and railroading were performed by a single operator. Ease of insertion, degree of manipulation (Jones Classification), post-operative sore throat, bleeding from oral cavity, haemodynamic changes and time to successful intubation were recorded and compared between the two groups. Results: There were no significant differences between ease of insertion (p=0.599), degree of manipulation (p=0.849), post-operative sore throat (p=0.15), bleeding from oral cavity (p=0.227) and time to intubation (p=488) between the two groups. Mean arterial pressure and heart rate changes were also not significant between the two groups (p=0.361 and p=0.152 respectively). Conclusion: Parker Flex Tip® ETT was comparable to Unoflex Reinforced™ ETT for orotracheal fibreoptic intubation in simulated difficult airway patients.